PENGARUH TIME BUDGET PRESSURE, SIFAT MACHIAVELLIAN, KOMPLEKSITAS TUGAS, STRES KERJA DAN ETIKA PROFESI TERHADAP PERILAKU AUDIT DISFUNGSIONAL (Studi Empiris pada KAP Korwil Sumatera Bagian Tengah dan Sumatera Bagian Selatan) - Yusaz, Agnisa Cesidahrila; Anisma, Yuneita; Rusli, Rusli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This research aims to determine the effect of time budget pressure, machiavellian nature, task complexity, job stress and professional ethics on dysfunctional audit behavior at Public Accounting Firms in Central Sumatera Region and Southern Sumatera Region. The data collection of this research was using questionnaire method that distributed to 115 auditors working at Public Accounting Firms in Central Sumatra Region and Southern Sumatera Region. The numbers of auditors who became research sample were 80 auditors from 23 Public Accounting Firms. Data analysis techniques used in this research was multiple linear regression analysis using SPSS 20 as data processing software program. The result of this research show that there is a significant relationship among time budget pressure, machiavellian nature, task complexity, job stress and professional ethics on dysfunctional audit behavior. The coefficient of determination (R²) shows that time budget pressure, machiavellian nature, task complexity, job stress and professional ethics simultaneously giving effect on dysfunctional audit behavior amounted to 59,80%. While the remaining 40,20% is influenced by other independent variable that are not observed in this research.Keywords : time budget pressure, machiavellian nature, task complexity, job stress, professional ethics, dysfunctional audit behavior